Specialities of the vegetation start and level of primary fruit set affect fruit quality - N. Rakonczás; P. Dremák; I. Gonda (International Journal of Horticultural Science, 2009)
Thinning is a h ighly crucial point of the apple production technology. According to results of numerous studies the earliest thinning is deemed to have the best amending effects. There can be considerable difference between trees of the same cul tivar and age in a plantation in respect to their flowering, in the numbers of fruits set and also in their canopy volume. Thus it can be crucial -just l ike in the case of pruning- to establish a fruit thinni ng su i ted for specif ic characteristics of actual trees. This experiment was established to examine how does primary fruit set (fruit load before thinning) and further on specific (fruit/TCS cm2) and absolute (fruit/tree) fruit-load of the trees affect quality attri butes at harvest. Our experiment was establ ished in a plantation on medium-tight loamy soil in north-east of Hungary. Harvest date was determined w ith the joint observation of the calendar date, starch-index, flesh firmness, background colour and fruit weight. Three fruit-load levels were established based on local experience and on data of several years, I Ot/ha lower and higher besides the advised optimum yield in the same orchard with slender-spindle shaped 'Gala must' cultivar standing on M9 rootstock in 1m x 3,8 m spacing. In the establishment of the 15, 25 and 35t/ha fruit-load levels on 20-20 apple trees total number of fruits set was counted at each tree. After this number of apples due to be removed was defined using an objective index on the basis of trunk cross sections (fruit/TCScm2) (Lafer, 1999). The following attributes were measured: weight (g), flesh firmness (lb/cm2) total soluble solid content (Brix %) and total titrate-able acid content (g/J).From the data on sugar and acid content quality index (Pomona value) was determined (Thialult, 1970). We could ascertain, that in an orchard, of the same aged but in concern to trunk cross sections somewhat different trees besides the specific index (apple/TCS cm2 the absolute fruit load (fruit/tree) can also be an important data, that has considerable effect on the internal quality. Secondly we could observe, that higher level of fruit load before thinning (primary fruit set) negatively affects quality index of the apples irrespective of the specific fruit load level (fruit/cm2 TCS) set later. Results underlines necessity of the earliest chemical thinn ing.